Natural mismatch repair mutations mediate phenotypic diversity and drug resistance in Cryptococcus deuterogattii - R Blake Billmyre (eLife, 2017)
Pathogenic microbes confront an evolutionary conflict between the pressure to maintain genome stability and the need to adapt to mounting external stresses. Bacteria often respond with elevated mutation rates, but little evidence exists of stable eukaryotic hypermutators in nature. Whole genome resequencing of the human fungal pathogen Cryptococcus deuterogattii identified an outbreak lineage characterized by a nonsense mutation in the mismatch repair component MSH2. This defect results in a moderate mutation rate increase in typical genes, and a larger increase in genes containing homopolymer runs. This allows facile inactivation of genes with coding homopolymer runs including FRR1, which encodes the target of the immunosuppresive antifungal drugs FK506 and rapamycin. Our study identifies a eukaryotic hypermutator lineage spread over two continents and suggests that pathogenic eukaryotic microbes may experience similar selection pressures on mutation rate as bacterial pathogens, particularly during long periods of clonal growth or while expanding into new environments.